Epidemiological analysis of polytrauma patients with kidney injuries in a university hospital - Guareschi,Bianca Luiza Valduga (2015)
Objective: To analyze the characteristics of trauma patients with renal lesions treated at a university hospital in Curitiba. Methods: We conducted a retrospective, cross-sectional study guided by review of medical records of trauma victims who underwent surgical treatment. The variables analyzed were age, gender, mechanism of injury, degree of kidney damage, conduct individualized according to the degree of renal injury, associated injuries, complications and deaths. We classified lesions according to the American Association of Trauma Surgery (TSAA). Results: We analyzed 794 records and found renal lesions in 33 patients, with mean age 29.8 years, most (87.8%) being male. Penetrating trauma accounted for 84.8% of cases. The most common renal injuries were grade II (33.3%), followed by grade I (18.1%), III, IV and V. Nephrectomy treated 45.4% of injuries, 73.3% being total nephrectomy, and 45.4% by nephrorraphy. In 9% treatment was non-surgical. Only 12.1% of patients had isolated renal lesions. Complications ensued in 15.1% and mortality was 6.06%. Conclusion: The surgical approach was preferred due to penetrating trauma mechanism. We achieved low rates of complications and deaths, and neither case could be directly related to kidney damage, and there were patients with multiple lesions. In this sample, we could not observe a direct relationship between kidney damage and complications, deaths or the type of conduct employed.